Internalization of Pancasila Values through Community Run Character Education in Palu City - Fath, Shofi Nurul; Sukri, Shara Rafiqa Nurulcholillah (Borobudur Educational Review, 2026)
Pancasila Education has often been implemented in a normative and predominantly cognitive manner, limiting the internalization of its values in real-life experience. This study examines how Pancasila values are internalized within a running community in Palu City as a form of experiential character education. Using a qualitative approach with an interpretative phenomenological design, the data were collected through in-depth interviews and participatory observation involving eight active members. The findings reveal that Divinity is expressed through reflection and gratitude; Humanity through empathy and sharing practices; Unity through inclusive togetherness across diverse backgrounds; Democracy through participatory dialogue; and Social Justice through equality and non-discrimination. Internalization occurs through embodied experience, sustained social interaction, habituation, and personal reflection. The running community functions as an effective non-formal pedagogical space for the transformative actualization of Pancasila values.